Hybrid methodology for parameter algebraic identification in spatial/time domain for switched reluctance motors - Carlos Vergara-Ramírez; John Cortés-Romero; Horacio Coral-Enriquez (Universitas Ahmad Dahlan, 2025)
The switched reluctance motor (SRM) has attracted attention in recent decades, due to its robustness, low manufacturing cost, and other performance characteristics. Thanks to the accepted and widely used mathematical model of this motor, model-based controllers, whose main foundation is the precise knowledge/identification of the motor parameters, are frequently reported in the literature and required in the industry. This article proposes a parametric identification for switching reluctance motors under an algebraic approach. The identification is based on the unsaturated model of the motor whose electrical parameters depend on the angular position. This work proposes an adaptation of the classic identification method defined in the spatial and temporal domains, due to the angular dependence on the electrical parameters and the temporal dependence on the mechanic parameters. In addition, the proposed identification strategy is simulated and experimentally validated in a DSP-based test bench. Reduced identification times, low error rates, and non-dependence of tuning parameters were obtained.